Issues In The Recruitment Of The Police Academy (Akpol) From The Perspective Of Good Governance Principles (A Study At The West Java Police Department In The 2017 Fiscal Year) - Suwito, Sidik Hadi (Journal of Law, Politic and Humanities, 2025)
The recruitment process for the Police Academy (Akpol) is based on the Republic of Indonesia Law Number 2 of 2002 concerning the Indonesian National Police and the Chief of Police’s Decree Number: Kep/186/II/2017 dated February 20, 2017, regarding the admission of Akpol cadets for the 2017 fiscal year. This decree states that the recruitment process is carried out in two stages: the regional-level selection conducted by the territorial units and the central-level selection held at the Akpol in Semarang. At the regional stage, the West Java Police Department (Polda Jawa Barat) is responsible for the recruitment process in its area, while Akpol Semarang handles the central-level selection. The implementation of good governance principles plays a crucial role in the Akpol recruitment process at the regional level, including at Polda Jawa Barat, to ensure that selected cadets are qualified individuals with the potential to become future leaders. This study aims to analyze the application of good governance principles in the regional-level Akpol recruitment, particularly at Polda Jawa Barat, using a qualitative approach and descriptive method. The results of the study indicate that several good governance principles were not fully implemented in the 2017 Akpol recruitment at Polda Jawa Barat, which led to controversy and disagreements in the recruitment process. The main issue arose due to the policy of the West Java Police Chief, which set a graduation quota based on special percentages for local and non-local candidates, causing controversy. As a result of this policy, the recruitment process at Polda Jawa Barat was eventually taken over by the National Police Headquarters (Mabes Polri) to ensure a more transparent implementation in accordance with the applicable regulations.